2015
DOI: 10.11113/jt.v74.4644
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodynamic Resistance analysis of New Hull Design for Multipurpose Amphibious Vehicle Applying with Finite Volume Method

Abstract: This paper numerically investigated the hydrodynamic resistance of Multipurpose Amphibious Vehicles (MAV) in three bow shapes to approach the better hull bow shape design. This type of vehicle and other blunt-shaped floating vehicles encounter the problem of a large bow wave forming at high speeds. This wave formation is accompanied by higher resistance and at a critical speed results in bow submergence or swamping. Three new shapes of hull bow design for the multipurpose amphibious vehicle were conducted at s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…High-accuracy hydrodynamic evaluation of the planned hull using CFD technology was studied (Sukas et al, 2017). The resistance of a multipurpose amphibious vehicle was studied using CFD techniques with Reynolds-averaged Navier-Stokes (RANS) model, which gives the viscous flow field around the hull (Nakisa et al, 2014). The CFD software STAR-CCM+ was used for the resistance prediction of an armored personnel carrier (APC) called BTR-80 (Islam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…High-accuracy hydrodynamic evaluation of the planned hull using CFD technology was studied (Sukas et al, 2017). The resistance of a multipurpose amphibious vehicle was studied using CFD techniques with Reynolds-averaged Navier-Stokes (RANS) model, which gives the viscous flow field around the hull (Nakisa et al, 2014). The CFD software STAR-CCM+ was used for the resistance prediction of an armored personnel carrier (APC) called BTR-80 (Islam et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the rapidity is usually limited by the shape of amphibious vehicles, such as bluntshape, which has poor hydrodynamics on water. In order to solve this problem, Adi Maimun et al 2,3 designed three shapes of hull bow for Multipurpose Amphibious Vehicle and used computational fluid dynamics (CFD) to study the resistance performance. They demonstrated that the U-shaped hull bow could reduce the total resistance by 20.3% and avoid swamping by water.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, most of these amphibious vehicles are designed for land operations only and their operations in water are limited to passing through rivers safely at a specified speed without satisfying floatation requirements. Therefore, the floatability and stability requirements of these vehicles are optional features required only for shallow water river operations (Nakisa, et al 2015).…”
Section: Introductionmentioning
confidence: 99%